Judicial Reasoning on Criminal Sanctions in Court Decision: Comparation between Indonesia and Uzbekistan - Faisal Faisal; Turdialiev Mukhammad Ali Polatjon Ogl (Universitas Muhammadiyah Surakarta, 2025)
ABSTRACT Purpose of the Study: This study aims to provide an in-depth analysis on the judicial reasoning and ratio decidendi in Decision No. 4/Pid.Sus-Anak/2022/PN Lbh on juvenile theft in Indonesia, especially regarding how judges interpret the element of offense, assess the risk of recidivism, and balance child protection and the need to maintain social order. This study also places this decision in a comparative context with the practice of juvenile penalization in Uzbekistan to strengthen the analysis. Methodology: This research employed the normative-juridical method with a case approach on a decision on a juvenile crime in Indonesia. The analysis was added with a statute approach on the Law on the Juvenile Criminal Court System, the Indonesian Criminal Code, and the Criminal Code of Uzbekistan. It also applied the conceptual approach, which encompasses the restorative justice theory, the best interest of the child theory, and the penalization theory. The analysis was conducted on a criminal case of theft in Indonesia, which involved children as perpetrators It also analyzed a juvenile criminal case of theft in Uzbekistan and its Criminal Code as a comparison. The primary legal materials consisted of Indonesian court decisions and a juvenile court decision in Uzbekistan. The secondary legal materials consisted of scientific journals, official papers, and relevant literary materials. The technique of analysis was carried out in a descriptive-qualitative manner to reconstruct judges’ juridical considerations and the ratio decidendi structure. Results: Results show that judges arrange reasoning through three main pillars: (1) evidencing of the offense element and the fulfillment of the aggravation element, (2) recidivism is a determinant that increases the criminogenic risk escalation. Thus, it demands a firmer intervention, and (3) the integration of Correctional Centers’ recommendations to guarantee that correctional activities for children are conducted in a structured environment. The decision states that for juvenile crimes, the imprisonment sanction is not sensed as a retributive sanction, but rather as a corrective instrument that is still based on the principle of the best interests of the child. Comparative analyses show that Uzbekistan faces a similar dilemma: restorative policies still give room for the selective use of imprisonment sanctions in the case of recidivism. Applications of this Study: This research provides an empirical reference for policymakers, academicians, and legal practitioners to understand the pattern of judges’ argumentation in juvenile cases. It also serves as a basis to strengthen policies on proportional penalization that are oriented towards rehabilitative actions and are responsive to the risk of recidivism. These findings are relevant to formulate socio-psychological assessment policies, guidelines to juvenile sentencing, and to strengthen Correctional Centers’ recommendation mechanism. Novelty/Originality of this Study: The novelty of this research lies in the systematic analysis of the ratio decidendi of a juvenile sentencing decision, which considers children’s psychological condition and the principle of the best interest of the child in forming a decision order. This study also adds a comparative perspective with Uzbekistan that is seldom discussed in Indonesian jurisprudential literature, enriching the understanding on global trends related to juvenile sentencing. Keywords: Judicial Reasoning, Ratio Decidendi, Juvenile Sentencing, Juvenile Criminal Court System, Child Offenders. ABSTRAK Tujuan Studi: Studi ini bertujuan untuk memberikan analisis mendalam tentang penalaran yudisial dan ratio decidendi dalam Keputusan No. 4/Pid.Sus-Anak/2022/PN Lbh tentang pencurian oleh anak di Indonesia, khususnya mengenai bagaimana hakim menafsirkan unsur tindak pidana, menilai risiko residivisme, dan menyeimbangkan perlindungan anak dan kebutuhan untuk menjaga ketertiban umum. Studi ini juga menempatkan keputusan ini dalam konteks komparatif dengan praktik penindakan anak di Uzbekistan untuk memperkuat analisis. Metodologi: Penelitian ini menggunakan metode normatif-yuridis dengan pendekatan kasus pada keputusan tentang kejahatan anak di Indonesia. Analisis ditambahkan dengan pendekatan undang-undang pada Undang-Undang tentang Sistem Pengadilan Pidana Anak, KUHP Indonesia, dan KUHP Uzbekistan. Penelitian ini juga menerapkan pendekatan konseptual, yang mencakup teori keadilan restoratif, teori kepentingan terbaik anak, dan teori penindakan. Analisis ini dilakukan pada kasus pidana pencurian di Indonesia yang melibatkan anak-anak sebagai pelaku (Putusan Pengadilan No. 4/Pid.Sus-Anak/2022/PN Lbh). Analisis ini juga menganalisis kasus pidana pencurian anak di Uzbekistan dan KUHP Uzbekistan sebagai perbandingan. Materi hukum primer terdiri dari putusan pengadilan Indonesia dan putusan pengadilan anak di Uzbekistan. Materi hukum sekunder terdiri dari jurnal ilmiah, dokumen resmi, dan literatur terkait. Teknik analisis dilakukan secara deskriptif-kualitatif untuk merekonstruksi pertimbangan yuridis hakim dan struktur ratio decidendi. Hasil: Hasil menunjukkan bahwa hakim menyusun penalaran melalui tiga pilar utama: (1) pembuktian unsur tindak pidana dan pemenuhan unsur pemberatan, (2) residivisme merupakan determinan yang meningkatkan eskalasi risiko kriminogenik. Oleh karena itu, diperlukan intervensi yang lebih tegas, dan (3) integrasi rekomendasi Lembaga Pemasyarakatan untuk menjamin bahwa kegiatan pemasyarakatan bagi anak-anak dilakukan dalam lingkungan yang terstruktur. Keputusan tersebut menyatakan bahwa untuk kejahatan anak, sanksi penjara tidak dianggap sebagai sanksi pembalasan, melainkan sebagai instrumen korektif yang masih berdasarkan prinsip kepentingan terbaik anak. Analisis komparatif menunjukkan bahwa Uzbekistan menghadapi dilema serupa: kebijakan restoratif masih memberikan ruang untuk penggunaan sanksi penjara secara selektif dalam kasus residivisme. Aplikasi Studi Ini: Penelitian ini memberikan referensi empiris bagi para pembuat kebijakan, akademisi, dan praktisi hukum untuk memahami pola argumentasi hakim dalam kasus anak. Penelitian ini juga berfungsi sebagai dasar untuk memperkuat kebijakan tentang hukuman proporsional yang berorientasi pada tindakan rehabilitatif dan responsif terhadap risiko residivisme. Temuan ini relevan untuk merumuskan kebijakan penilaian sosial-psikologis, pedoman untuk penjatuhan hukuman terhadap anak, dan untuk memperkuat mekanisme rekomendasi Lembaga Pemasyarakatan. Kebaruan/Orisinalitas Studi Ini: Kebaruan penelitian ini terletak pada analisis sistematis mengenai ratio decidendi dalam putusan hukuman anak, yang mempertimbangkan kondisi psikologis anak dan prinsip kepentingan terbaik anak dalam membentuk suatu putusan. Studi ini juga menambahkan perspektif komparatif dengan Uzbekistan yang jarang dibahas dalam literatur yurisprudensi Indonesia, memperkaya pemahaman tentang tren global terkait dengan hukuman anak. Kata Kunci: Penalaran Yudisial, Ratio Decidendi, Hukuman Anak, Sistem Pengadilan Pidana Anak, Pelaku Kejahatan Anak